LEGALISASI DEWAN SYARIAH NASIONAL DAN KOMITE PERBANKAN SYARIAH DALAM PANDANGAN FIQHI EKONOMI PERBANKAN - Eka Dahlan Uar (IAIN Ambon, 2017)
Implementation of tasks and functions of National Council of Sharia and Committee of Islamic Banking is closely related to legislation of the banking economics Fiqh. In development of the Islamic banking, legalization between National Council of Sharia in a work meeting to make a recommendation for the Committee that can be enacted as the Bank Indonesia Regulation. Based on the analysis, it can be concluded that between implementation of the tasks and functions of National Council of Sharia in the Islamic economics sector has been implemented base on the decision of DSN-MUI. No.1, 2000 on the Basic Guidelines of the National Council of Shariah of Indonesian Ulama Council and Decision of DSN-MUI No. 02, 2000 on the Household Guidelines of National Council of Sharia of Indonesian Ulama Council, which has brought forth the decision in the form of fatwa as well as legalizing both institutions and made as the icon base for the implementation of banking economic in Indonesia. Keywords: National Council of Sharia, Committee of Islamic Banking, fiqh muamalah